Rupture distance and shape of the liquid bridge with rough surface. (15th June 2021) - Chen, Jian; Wang, Peipei; Li, Mengran; Shen, Jiahe; Howes, Tony; Wang, Geoff
Graphical abstract: Highlights: A VOF model was developed for liquid bridge rupture on rough surface. Effects of roughness and orientation on the rupture distance were analysed. Liquid redistribution after ruptured were analysed. Abstract: Liquid bridges have attracted great interest for many years in wide areas, including wet granular process, mineral processing, and flow in particle-formed porous media. Research to date has explored the liquid bridge force and rupture distance between surfaces of various shapes. However, the rupture of a large liquid bridge between rough surfaces is a problem of practical importance. This work investigated the rupture distance and shape of the liquid bridge formed between surfaces with different roughnesses, as well as the redistribution of the liquid after rupture. Firstly, some experiments on smooth surfaces were performed and a Volume of Fluid (VOF) model was established to provide a fundamental base for simulation of the liquid bridge behaviours on rough surfaces. This model was calibrated by the rupture experimental results and then applied to predict the effect of roughness on the liquid bridge rupture distance. The effect of contact angle and roughness on the rupture distance, shape and redistribution of the liquid bridge has been further analysed. It was shown that the roughness of the surfaces plays a significant role in rupture distance, particularly for relatively large roughness values.